Predição da emissão de metano entérico de bovinos Nelore - Pires Sobrinho, Tatiana Lucila [UNESP] (2015)
This work was conducted with the objective of developing enteric methane (CH4) emission prediction equations and to evaluate equations described in the literature as to accuracy, estimate the heritability of methane emission and linking this issue and feed efficiency of Nellore in growth under tropical conditions. Forty-eight Nellore were evaluated for dry matter intake, nutrient intake and methane emission and equations were generated based on consumption data and evaluated by the square root of the mean square prediction error (RMSE) and residual regression. From the methane emission in vivo data, equations described in the literature were validated, assessed according to the same criteria used for the new generated equations. To estimate the heritability of individual consumption, data were used and body weight of 896 Nellore (541 males and 355 females) with an average initial body weight of 276±53 kg, born between 2004 and 2012 (286±39 days old) and assessed for residual feed intake (RFI). An equation generated from dry matter intake of 48 animals evaluated was used to estimate methane emissions from the other 896 animals, and two other equations described by Ellis et al also used for the same purpose. The heritability of methane emission was estimated for each equation. Equations including the variables dry matter intake and consumption of hemicellulose, dry matter intake and intake of total carbohydrates, metabolizable energy intake and consumption of pulp and consumption of non-fiber carbohydrates had the lowest RMSE values, are considered the most adjusted to the data set studied. Five of the 17 equations described in the literature could predict methane emissions properly to the lowest RMSE values among the evaluated equations. However, the equations developed in this study were more accurate in predicting the methane emission evaluating under the same parameter. The heritability estimate (h2) of CH4 showed high magnitude ...